Knowledge and prejudices about mental health in outpatients' relatives in Cayetano Heredia Hospital - Castro Cuba Torres, Pedro (2013)
Objectives: To describe knowledge and prejudices about mental health and to determine if there is any association between demographic characteristics, health knowledge and prejudices on mental health.   Materials and Method: This is a cross-sectional descriptive study. Three vignettes describing typical cases of depression, panic disorder, and schizophrenia were elaborated, and questions were asked about them. Vignettes and their questions were validated by a group of experts. Each vignette and its questions were administered to 151 relatives of persons attending the outpatient clinic for conditions other than psychiatric disorders, so 453 individual vignettes were assessed.   Results: For cases of panic disorder, interviewees preferred patients should be seen by a specialized non-psychiatrist physician (76,0%), and they also considered these patients might die because of an undiagnosed physical condition (57,3%). For cases of depression and schizophrenia, professionals chosen as the most adequate for managing these patients were psychologists (41,7% and 45,0%, respectively). For cases of schizophrenia, an association was found between going to the psychiatrist or having a mental disorder, and they also considered these subjects may represent a threat for their peers (p=0,003 and p<0,001, respectively).   Conclusions: A high percentage of interviewees would recommend that patients with schizophrenia or depression should be treated by a psychologist. On the other hand, they also considered that patients with panic disorder may have an undiagnosed physical condition and that they should be treated by a non-psychiatrist physician.